2020
DOI: 10.1002/jor.24858
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic changes in severe hip osteoarthritis measured at matched gait speeds

Abstract: Kinematic differences between patients with osteoarthritis (OA) and control participants have been reported to be influenced by gait speed. The purpose of this study was to experimentally detect the effect of walking speed on differences in spatiotemporal parameters and kinematic trajectories between patients with hip OA and age‐matched asymptomatic participants using wearable sensors and statistical parametric mapping (SPM). Twenty‐four patients with severe unilateral hip OA and 48 control participants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…joint loading on a daily basis ( Astephen Wilson, 2012 ). Additionally, it has been shown that gait modifications in people with HOA persist even at matched gait speeds ( Ismailidis et al, 2021 ). The application of ANCOVA neglects the fact that differences in gait speeds between groups are not a source of random error variability but rather representative of the population characteristics ( Astephen Wilson, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…joint loading on a daily basis ( Astephen Wilson, 2012 ). Additionally, it has been shown that gait modifications in people with HOA persist even at matched gait speeds ( Ismailidis et al, 2021 ). The application of ANCOVA neglects the fact that differences in gait speeds between groups are not a source of random error variability but rather representative of the population characteristics ( Astephen Wilson, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 29 had unilateral knee OA and were scheduled to undergo total knee arthroplasty, 30 had unilateral hip OA and were scheduled total hip arthroplasty, and 54 were age-matched asymptomatic persons ( Table 1 ). Subsets of data have been published previously in studies focusing on differences in gait kinematics between limbs in patients with knee OA and compared to healthy controls [ 21 , 23 ] and on differences in gait kinematics between limbs in patients with hip OA and compared to healthy controls [ 22 , 24 ]. For the current analysis, we expanded all groups of participants and focused on detecting differences in joint kinematics between patients with knee OA and patients with hip OA.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, for patients with knee OA, differences in stride duration, knee flexion range of motion (ROM) in swing and stance have been assessed using the GaitWalk system [ 18 ], kinematic differences at the hip, knee and ankle in the sagittal plane using the H-Gait system [ 19 ], and thigh and shank sagittal and coronal, knee sagittal kinematics as well as temporal gait parameters using the GaitSmart TM system [ 20 ]. In a series of studies, Ismailidis et al have shown that known differences in joint kinematics between patients with knee OA [ 21 ] or patients with hip OA [ 22 ] and healthy controls can be measured using the RehaGait ® system, reported kinematic differences not only for the index joint but also to adjacent joints, and confirmed that some of these differences depend on walking speed [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings from these studies suggest that information extracted from the raw acceleration or angular velocity signals, even from a single sensor, may be useful to discriminate between people with knee OA and controls and could be related to clinically meaningful participant-reported outcomes. Barrois et al, 2016 [23] Trained machine learning pipeline to estimate hip and knee joint loading; error too large for clinical use Single IMU c (Samsung Galaxy J5 2017, Samsung) inside cell phone, attached to hip Hip OA (n=20) De Brabandere et al, 2020 [31] Automatically extracted features gave best machine learning accuracy in discriminating THA from healthy individuals 7 IMU c (Awinda, Xsens Technologies BV) on feet, shanks, thighs, and back Healthy (n=27) and THA d (n=20) Dindorf et al, 2020 [32] Significant changes in hip and knee kinematics exist between hip OA and healthy individuals in speed matched conditions 7 IMU b (RehaGait, Hasomed) on pelvis, feet, shanks, and thighs Healthy (n=48) and hip OA (n=24) Ismailidis et al, 2020 [61] Significant differences in all spatiotemporal parameters between groups when walking at self-selected speed 7 IMU b (RehaGait) on pelvis, feet, shanks, and thighs Healthy (n=28) and knee OA (n=23) Ismailidis et al, 2020 [26] Linear acceleration (significant) and jerk (insignificant) negatively associated with self-reported instability 5 IMU c (3D myoMOTION, Noraxon) on pelvis, thighs, and shanks Healthy (n=13) and knee OA (n=26) Na and Buchanan, 2021 [25] Stance and double support ratio 2 most consistent discriminating features between OA and controls 2 IMU b (Shimmer3, Shimmer Sensing) on feet Healthy (n=10) and knee OA (n=10)…”
Section: Assessment Of Oa Presence and Severitymentioning
confidence: 99%
“…Other studies have used more computationally complex approaches to extract spatiotemporal parameters and joint kinematics during walking using IMU data. Ismailidis et al [26,61] published 2 studies, one each in people with end-stage hip OA and those with end-stage knee OA, in which they compared spatiotemporal and sagittal plane kinematics from IMUs between OA and control populations. Using statistical parametric mapping, they observed differences in multiple parameters (eg, cadence, knee, and hip kinematics) between each OA population and controls.…”
Section: Assessment Of Oa Presence and Severitymentioning
confidence: 99%